Cystic artery pseudoaneurysm secondary to acute cholecystitis as cause of haemobilia - Siddiqui, Nadeem Ahmed (BMJ Publishing Group, 2011)
Formation of cystic artery pseudo aneurysm is a rare complication of a common problem that is, acute cholecystitis. Here the authors present a case of 58-year-man with history of upper abdominal pain and fever. Ultrasound initially showed huge subhepatic collection and distended gall bladder with gall stones. Later on, CT scan showed the cystic artery pseudo aneurysm in the wall of gall bladder. Selective angioembolisation of cystic artery followed by elective open cholecystectomy was done and patient recovered well postprocedure. Pathology report later on showed xanthogranulomatous cholecystitis. Case emphasises the need of high index of suspicion to diagnose this rare entity, which in this case was successfully treated with two staged approach that is, angioembolisation of aneurismal vessel and then interval open cholecystectomy.